2020
DOI: 10.1002/anie.202003670
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Toxic HCN During NOx Removal by Ammonia SCR in the Exhaust of Lean‐Burn Natural Gas Engines

Abstract: Reducing greenhouse gas and pollutant emissions is one of the most stringent priorities of our society to minimize their dramatic effects on health and environment. Natural gas (NG) engines, in particular at lean conditions, emit less CO2 in comparison to combustion engines operated with liquid fuels but NG engines still require emission control devices for NOx removal. Using state‐of‐the‐art technologies for selective catalytic reduction (SCR) of NOx with NH3, we evaluated the interplay of the reducing agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…In addition to the blockage of the surface sites, the effect of competing reactions should be considered as well. Thus, the formation of high HCN concentrations suggests a simultaneous reaction of NH 3 with HCHO, which is a propylene oxidation byproduct [36]. The enhancement of pressure also promotes the NO x conversion for Cu-SSZ-13 and, as expected, compensates the negative impact of C 3 H 6 presence.…”
Section: Impact Of Elevated Pressure and Hydrocarbon Presence On No X Conversionsupporting
confidence: 51%
See 2 more Smart Citations
“…In addition to the blockage of the surface sites, the effect of competing reactions should be considered as well. Thus, the formation of high HCN concentrations suggests a simultaneous reaction of NH 3 with HCHO, which is a propylene oxidation byproduct [36]. The enhancement of pressure also promotes the NO x conversion for Cu-SSZ-13 and, as expected, compensates the negative impact of C 3 H 6 presence.…”
Section: Impact Of Elevated Pressure and Hydrocarbon Presence On No X Conversionsupporting
confidence: 51%
“…The only notable difference was a sudden formation of significant amounts of hydrogen cyanide (29 ppm HCN at 500 • C, Table 2). Recent studies have shown that HCN can be formed by the reaction of NH 3 and HCHO over conventional SCR catalysts [36][37][38]. Since the conversion of propylene over Fe-ZSM-5 leads to a large amount of HCHO, this is most probably directly involved in HCN formation.…”
Section: Hydrocarbon Oxidation At Elevated Pressure In the Presence Of Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…Future exhaust gas aftertreatment systems may be amended by implementing a state-of-the-art urea-based SCR system for NO x control in addition to the oxidation catalyst. This necessitates a careful choice of both, engine operation parameters for controlling engine-out emissions and catalyst formulation for minimizing secondary emissions, for instance since HCHO and NH 3 can form highly toxic HCN over several SCR catalysts [32,33]. However, as this approach is already well-established in the context of lean-burn diesel engines, the technological hurdles for extending the overall system are expected to be moderate, allowing a fast realization and transfer into serial production.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The formation of highly toxic HCN was even reported, formed from NH 3 and formaldehyde, molecules that are typically present in the exhaust gases of NH 3 -SCR system fitted to natural gas engines. 9 NO decomposition to N 2 and O 2 is strongly favoured below 450°C, as the equilibrium concentration of NO x (= NO + NO 2 + N 2 O) is lower than 1 ppm when starting with a reaction mixture comprising 200 ppm NO + 10% O 2 in N 2 (Fig. 1).…”
mentioning
confidence: 99%